Advancing cancer control efforts in Nigeria: reflections on World Cancer Day 2022 in a vulnerable state in Nigeria - A. Oyeyemi; A. Adesina; T. Awudu (World Cancer Research Journal, 2022)
Objective: Cancer, the second leading cause of death globally, disproportionately affects low- and middle-income countries (LMICs) like Nigeria. World Cancer Day (WCD) is one of several interventions to increase awareness of the disease. Bayelsa State is desirous of reducing its cancer burden and is making efforts in that regard. The objective of this paper is to describe the activities conducted in the oil-rich and cancer-prone Bayelsa State of Nigeria to commemorate WCD 2022.